Author Correction: Mitochondrial DNA synthesis fuels NLRP3 inflammasome. Issue 12 (December 2018) - Coll, Rebecca; Holley, Caroline; Schroder, Kate
In the initial published version of this article, there was a mistake in the title. The correct title should be "Mitochondrial DNA synthesis fuels NLRP3 activation". This correction does not affect the description of the results or the conclusions of this work.